Antecedentes históricos de la “abogacía telúrica” desarrollada en Chile entre los siglos XVI y XIX - Alfredo Palacios Roa (Historia Crítica, 2014)
The earthquakes that struck Chile between the 16th and 19th centuries — together with the lack of rational explanations of their causes — led the settlers of the Kingdom of Chile, as well as many inhabitants of the cities founded on the western margin of the Circumpacific Belt, to interpret them as punishments sent by God as a result of their worldly faults and sins. Consequently, some groups had to resort to the designated “celestial lawyers,” specialists in telluric matters, to try to overcome the conjunctural situations generated by every earthquake.